International Secondary Science Grade 6 work book - Catherine Jones; Catherine Jones (Karachi Oxford University press, 2025)
International Secondary Science has been developed in accordance with the guidelines of Pakistan National Curriculum 2022 framework. The textbooks are divided into the areas of physics, biology, and chemistry.